Pengaruh Strategi Adaptasi Perubahan Iklim Terhadap Ketahanan Pangan Rumah Tangga Petani Padi di Desa Jenggolo, Kecamatan Kepanjen, Kabupaten Malang - Ainina, Shafa; Rini Mutisari; Tatiek Koerniawati; Deny Meitasari (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
This study explores the relationship between climate change adaptation strategies and household food security among rice farmers in Jenggolo Village, Kepanjen District, Malang Regency. Unlike previous research that primarily examines the impact of climate change on agricultural productivity, this study focuses on how adaptation strategies influence household-level food security. Using descriptive analysis, the Household Food Insecurity Access Scale (HFIAS), Propensity Score Matching (PSM), and probit regression, the study identifies adaptation strategies, measures food security levels, and evaluates factors affecting farmers' decisions to adopt these strategies. Results show that farmers adopting intensive adaptation strategies (three or more) tend to have better food security compared to those adopting fewer strategies. Socio-demographic factors, such as family size, education, participation in farmer groups, and land ownership, significantly influence these decisions. Strengthening farmer access to resources and comprehensive adaptation efforts is essential to improving household food security amid ongoing climate risks.